Advanced Aqueous Zinc‐Ion Batteries Enabled by 3D Ternary MnO/Reduced Graphene Oxide/Multiwall Carbon Nanotube Hybrids. Issue 4 (6th March 2021) - Mao, Xianxing; Zhang, Xinyi; Zeng, Yanfei; Halima, Ahmed Farid; Shen, Pei Kang
Abstract : Aqueous zinc‐ion batteries (AZIBs) are becoming increasingly popular energy storage technology compared with conventional lithium‐ion and other rechargeable batteries. However, the poor structural stability and low conductivity remain a significant challenge in the development of the cathode material. This renders AZIBs with limitation of commercial secondary batteries. Herein, cathode optimization is demonstrated through precise control of the coupling of MnO with reduced graphene oxide (rGO) and multiwall carbon nanotubes (MWCNTs). 3D ternary MnO/rGO/MWCNTs (MPGC) nanostructures are synthesized by combining MnO nanoparticles with rGO and MWCNTs using a scalable hydrothermal and solid thermal reduction method. The MPGC cathode delivers a high specific capacity of 267.4 mAh g −1 at 0.2 A g −1 and improved stability with retention rate of 96.2% after 200 cycles at 0.5 A g −1 and 94.7% after 550 cycles at 1.2 A g −1 . This simple synthesis method has great potential in practical application of AZIBs as next‐generation rechargeable batteries. Abstract : The development of optimized Mn‐based oxide integrated with reduced graphene oxide in a 3D porous multiwall carbon nanotubes' (MWCNT) framework is presented. The cathodes display excellent performance by maintaining a specific capacity of 267.4 mAh g −1 at 0.2 A g −1 and 115.9 mAh g −1 at 1.2 A g −1 with improved stability as evidenced by a retention rate of 94.7% after 550 cycles at 1.2 A g −1 .